IMPACT OF Pleurotus tuber-regium(Rumph. ex Fr.)EXTRACT LOADED SILVER NANOPARTICLES ON LIPID PROFILE OF MAMMALIAN MODEL,WISTAR ALBINO RATS(Rattus norvegicus) - DANDAPAT, SUKUMAR; KUMAR , MANOJ; SRIVASTAVA, ROHIT; SINHA, MANORANJAN PRASAD (The Bioscan, 2023)
The effect of silver nanoparticles (SNPs) loaded with Pleurotus tuber-regium extract on the lipid profile of Wistar albino rats as mammalian model has been assessed and compared with that of crude extract.The SNPs loaded with P. tuber-regium extract showed significant (p<0.05) increase in HDL (High Density Lipoprotein) cholesterol (52.74±1.12 mg dL-1) in rats treated with 400 mg kg-1 dose (group 3) of nanoparticles in comparison to 200 mg kg-1 dose (group 2) and control group (group 1). However, a significant decrease (p<0.05) in total cholesterol (65.24±0.70 mg dL-1), LDL cholesterol (29.82±0.29 mg dL-1) and triglyceride (63.91±0.99 mg dL-1) in rats of Group-3 was observed compare to the Group-2 and control group of rats. The results of SNPs treatment, when compared to the crude extract treatment for the similar parameters, have shown significantly (p<0.05) better performance. The medicinal properties of SNPs exhibited better efficacy than the crude extract. On the basis of the observations, it can be concluded that crude extract of Pleurotus tuber-regium as well as silver nanoparticles loaded with extract of Pleurotus tuber-regium be used in formulation and delivery of drug for hypercholesterolemia.